The Development of Interactive Multimedia Raya Based on Local Wisdom Fire War in Buduk Village Pancasila Education Content for Fifth Grade Elementary Students - Ni Komang Manik Mas Safitri; Didith Pramunditya Ambara; Ni Luh Putu Agetania (MIMBAR PGSD Undiksha, 2024)
The rapid development of 21st-century technology plays a crucial role in various aspects of life, including education. However, the limited use of technology-based learning media often leads to student boredom, decreased motivation, and difficulty understanding learning content. This study aims to develop and evaluate the effectiveness of the RAYA interactive multimedia based on local wisdom, specifically designed to enhance conceptual understanding and cultural awareness in Pancasila Education for fifth-grade elementary students. The research employed the ADDIE development model involving stages of analysis, design, development, implementation, and evaluation. Data were collected through questionnaires, multiple-choice tests, and expert validation, involving 1 content expert, 1 media expert, 1 class teacher, and 11 fifth-grade students as trial subjects. Data analysis techniques included descriptive qualitative, descriptive quantitative, and inferential statistical analysis using a t-test. The results indicate that the developed multimedia is categorized as good by experts and users. Furthermore, the effectiveness test shows a significant improvement in students' learning outcomes with tcount = 12.266 > ttabel = 1.701 at a 5% significance level. These findings demonstrate that RAYA interactive multimedia effectively improves students’ conceptual mastery and cultural literacy in Pancasila Education. The implication of this research suggests that integrating local wisdom into interactive media can enhance learning outcomes and preserve cultural values among elementary school students.